Mathematical Model of Cervical Cancer Treatment Using Chemotherapy Drug - Murtono Murtono; Meksianis Zadrak Ndii; Sugiyanto Sugiyanto (Biology, Medicine, & Natural Product Chemistry, 2019)
Cervical cancer is a malignant disease that causes problems in women's health, especially in developing countries such as Indonesia. Cervical cancer cells will develop quickly, uncontrollably, and will continue to divide and then infiltrate the surrounding tissue and continue to spread to connective tissue, blood, and attack important organs and spinal nerves. The aim of the research is to study the mathematical model of cervical cancer by chemotherapy treatment. The results of this study are that cervical cancer treatment using chemotherapy is effective enough to kill abnormal cells such as infected cells, pre-cancerous cells and cancer cells, although there are side effects, namely the killing of normal cells due to chemotherapy drugs.